Analytical free energy gradient for the molecular Ornstein-Zernike self-consistent-field method - Yoshida, N. (Condensed Matter Physics, 2007)
An analytical free energy gradient for the molecular Ornstein-Zernike self-consistent-field (MOZ-SCF) method
is presented. MOZ-SCF theory is one of the theories to considering the solvent effects on the solute electronic
structure in solution. [Yoshida N. et al., J. Chem. Phys., 2000, 113, 4974] Molecular geometries of water,
formaldehyde, acetonitrile and acetone in water are optimized by analytical energy gradient formula. The
results are compared with those from the polarizable continuum model (PCM), the reference interaction site
model (RISM)-SCF and the three dimensional (3D) RISM-SCF. Представлено аналiтичний вираз для градiєнта вiльної енергiї в методi молекулярне рiвняння Орнштейна-Цернiке – самоузгоджене поле (MOZ-SCF). Теорiя MOZ-SCF є однiєю з теорiй для розгляду ефектiв розчинника на електронну структуру молекул розчинюваної речовини в розчинi. Молекулярна геометрiя молекули води, формальдегiду, ацетонiтрилу i ацетону у водi оптимiзованi за допомогою аналiтичної формули для енергiї. Отриманi результати порiвнюються з результатами, отриманими в рамках поляризацiйної континуальної моделi (PCM), моделi базисних силових центрiв (RISM)–SCFi тривимiрного (3D)RISM–SCF.